Comparison of mean diffusivity, R2* relaxation rate and morphometric biomarkers for the clinical differentiation of parkinsonism. (March 2023) - Chougar, Lydia; Lejeune, François-Xavier; Faouzi, Johann; Morino, Benjamin; Faucher, Alice; Hoyek, Nadine; Grabli, David; Cormier, Florence; Vidailhet, Marie; Corvol, Jean-Christophe; Colliot, Olivier; Degos, Bertrand; et al.
Abstract: Introduction: Quantitative biomarkers for clinical differentiation of parkinsonian syndromes are still lacking. Our aim was to evaluate the value of combining clinically feasible manual measurements of R2* relaxation rates and mean diffusivity (MD) in subcortical regions and brainstem morphometric measurements to improve the discrimination of parkinsonian syndromes. Methods: Twenty-two healthy controls (HC), 25 patients with Parkinson's disease (PD), 19 with progressive supranuclear palsy (PSP) and 27 with multiple system atrophy (MSA, 21 with the parkinsonian variant -MSAp, 6 with the cerebellar variant -MSAc) were recruited. R2*, MD measurements and morphometric biomarkers including the midbrain to pons area ratio and the Magnetic Resonance Parkinsonism Index (MRPI) were compared between groups and their diagnostic performances were assessed. Results: Morphometric biomarkers discriminated better patients with PSP (ratio: AUC 0.89, MRPI: AUC 0.89) and MSAc (ratio: AUC 0.82, MRPI: AUC 0.75) from other groups. R2* and MD measurements in the posterior putamen performed better in separating patients with MSAp from PD (R2*: AUC 0.89; MD: AUC 0.89). For the three-class classification "MSA vs PD vs PSP", the combination of MD and R2* measurements in the posterior putamen with morphometric biomarkers (AUC: 0.841) outperformed each marker separately. At the individual-level, there were seven discordances between imaging-based prediction and clinical diagnosis involving MSA. Using the new Movement Disorder Society criteria for the diagnosis of MSA, three of these seven patients were clinically reclassified as predicted by quantitative imaging. Conclusion: Combining R2* and MD measurements in the posterior putamen with morphometric biomarkers improves the discrimination of parkinsonism. Highlights: R2* and MD measurements in the posterior putamen are robust clinically usable biomarkers for the discrimination of MSAp. Their combination with brainstem morphometric biomarkers increases the performance of the multiclass classification "MSA versus PD versus PSP". Concordance between MRI-based diagnostic prediction and clinical diagnosis was improved using the new diagnostic criteria for MSA.